Mutations of RAS genes identified in acute myeloid leukemia affect glycerophospholipid metabolism pathway - Liang, Tianqi; Kong, Yanxiang; Xue, Hongman; Wang, Wenqing; Li, Chunmou; Chen, Chun (Frontiers in Oncology, 2023)
Acute myeloid leukemia (AML) is a malignant disease originating from myeloid hematopoietic stem cells. The survival outcomes of AML are mainly related to cytogenetic changes and gene mutations. Recent studies have shown that certain gene mutations promote tumor cell survival and affect the prognosis of patients by affecting metabolic mechanisms in tumor cells. RAS gene mutations are prevalent in AML, and the RAS signaling pathway is closely related to many metabolic pathways. However, the effects of different RAS gene mutations on AML cell metabolism are unclear. In this study, we compared full-transcriptome data of Ba/F3 cells before and after RAS gene mutation and found that differentially expressed genes after NRAS Q61K and KRAS G12V mutation were associated with the lipid metabolism pathway. Moreover, by comparing groups, we found that the expression of the DGKzeta and PLA2G4A genes in the glycerophospholipid metabolism pathway was significantly upregulated. In conclusion, our study revealed that RAS gene mutation is closely related to the glycerophospholipid metabolism pathway in Ba/F3 cells, which may contribute to new precision therapy strategies and the development and application of new therapeutic drugs for AML.